2012
DOI: 10.4021/gr392w
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Percutaneous Endoscopic Gastrostomy on Quality of Life in Patients With Dementia

Abstract: BackgroundTo examine the effects of percutaneous endoscopic gastrostomy (PEG) on quality of life (QOL) in patients with dementia.MethodsWe retrospectively included 53 Japanese community and tertiary hospitals to investigate the relationship between the newly developed PEG and consecutive dementia patients with swallowing difficulty between Jan 1st 2006 and Dec 31st 2008. We set improvements in 1) the level of independent living, 2) pneumonia, 3) peroral intake as outcome measures of QOL and explored the factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 13 publications
1
10
0
1
Order By: Relevance
“…As the Japanese society ages, it is expected that PEG‐constructed patients will age as well. Recently, although clinicians tend to avoid PEG construction for prolonging life among older dementia patients, it has been reported that PEG can be expected to improve the quality of life for mild dementia patients 6 . In the present study, all patients who experienced bleeding after PEG procedure were aged >65 years.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…As the Japanese society ages, it is expected that PEG‐constructed patients will age as well. Recently, although clinicians tend to avoid PEG construction for prolonging life among older dementia patients, it has been reported that PEG can be expected to improve the quality of life for mild dementia patients 6 . In the present study, all patients who experienced bleeding after PEG procedure were aged >65 years.…”
Section: Discussionmentioning
confidence: 71%
“…Recently, although clinicians tend to avoid PEG construction for prolonging life among older dementia patients, it has been reported that PEG can be expected to improve the quality of life for mild dementia patients. 6 In the present study, all patients who experienced bleeding after PEG procedure were aged >65 years. Therefore, it is important to clarify the early signs that predict bleeding requiring additional treatment during perioperative periods.…”
Section: Figurementioning
confidence: 85%
“…The following underlying factors might account for the gender distribution of patients: Firstly, the patients with PEG were predominantly female (64%) at the Nishimaruyama Hospital, and the 3:7 (male:female) ratio was close to those reported in other studies. 10) Secondly, the risk factors for poor survival in patients with dementia includes male gender 14) ; thus, more females tended to survive, which may explain the all-female composition our patient population.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies reported the rate of PEG tube removal in Japan as 1.7% and 6.5%, respectively. 10,11) However, no studies have thus far explored patients who resume full oral intake after removal of PEG tubes.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a safe procedure that can reduce the burden on the patients as much as possible is required [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%